Nuts: An Autoethnographic Creative Nonfiction Imagination of Mad-Affirming Dance Spaces - Smorschok, Megan (Art/Research International)

(untitled) (University of Alberta, 2023)
The following fairy tale is the creative output from an arts-based autoethnographic inquiry created in partial fulfillment for my Master of Arts degree. Inspired by the doctoral work of Lindsay Eales (2018), my main research objective was to challenge, (re)imagine, and transform conventional dance spaces into spaces that were more accessible for Mad bodyminds. I used artistic processes such as painting, dancing, and journaling to examine my own experiences of madness within and outside of dance spaces. I then took my findings and began writing an autoethnographic creative nonfiction piece in the form of a whimsical fairy tale that sought to deconstruct my personal experiences and reconnect them to other Mad works and texts. In doing so, my fairy tale is not only an imagination of the Mad-affirming dance spaces I wish were available to me throughout my dance career, it is an invitation to imagine Mad-affirming worlds beyond.